ERIOCAULACEAE OF RICE FIELDS OF BILASPUR IN CHHATTISGARH - Moghe, Snehal; Dubey, Veenapani (Current Botany, 2017)
During our field visits in Rice fields of Bilaspur, Chhattisgarh we found 3 species of Eriocaulon belonging to family Eriocaulaceae, commonly known as ‘Pipe wort’ family (Haines,1921). Though it was not very common, it’s interesting and complicated morphological features made us to view this species from a different angle. These have been discussed in present paper. Keys words: Eriocaulon, rice field, Pipeworts, Eriocaulon quinguangulare.